Dance teaching at school in optical teachers of Physical Education and Art - SOUSA, Nilza Coqueiro Pires de; HUNGER, Dagmar Aparecida Cynthia França; CARAMASCHI, Sandro (Brazilian journal of physical education and sport, 2014)
The aim of this descriptive study, qualitative and quantitative in nature, was to analyze whether the content is broken down on the dance Political Pedagogical Project (PPP) in the Schools; presents itself as teaching dance classes in Physical Education and Art, which the teachers' knowledge of content in dance recommended National Curriculum, where importance is given to teaching dance at school and what are its limits. It was used a questionnaire with open and closed issues for sixty-four effective teachers of art and physical education of the public State and municipal network of a city in the State of São Paulo in Brazil. In summary, it was found that these teachers do not have an effective and collective participation during the process of construction of the PPP education; they know, but apply very little and with restrictions on the contents of dance suggested by PCN's of their respective disciplines, are basically relegated to the festivities school and dance are the difficulties faced by many teachers in the school dance. We conclude as necessary to unite and integrate these educators in favor of contents school dance, so she effectively occupy its space in Physical Education classes and Art.